Electrodeposition of Pt3Sn Nano‐alloy on NiFe‐Layered Double Hydroxide with "Card‐house" Structure for Enhancing the Electrocatalytic Oxidation Performance of Ethanol. Issue 3 (9th February 2021) - Xiang, Qiankun; Xu, Yanqi; Chen, Rongrong; Yang, Caihong; Li, Xuemei; Li, Guangyao; Wu, Di; Xie, Xiangli; Zhu, Wenfeng; Wang, Linjiang
Abstract: Catalysts are an important part of the ethanol fuel cell. However, catalysts present certain problems such as high cost, low conversion efficiency, and poor durability, which hinder the commercialization of direct ethanol fuel cells. The method of loading the catalyst on the carrier and alloying can effectively improve the dispersion, enhance the anti‐poisoning ability, improve stability, and reduce cost of the catalyst. In this work, NiFe‐layered double hydroxide (NiFe‐LDH) with a "card‐house" structure was grown vertically on nickel foam by electrochemical deposition. Pt3 Sn nano‐alloy particles were then deposited on NiFe‐LDH/NF by electrochemical deposition to generate the ethanol electrocatalytic material (denoted as Pt3 Sn NPs/NiFe‐LDH/NF). The "card‐house" structure formed by NiFe‐LDH thin nanosheets (thickness of 14.63 nm) improved the dispersion and uniformity of the Pt3 Sn nano‐alloy particles (5.34 nm). The introduction of the oxyphilic metals Ni and Fe enhanced the anti‐toxicity of the Pt3 Sn nano‐alloys. The synthesized catalyst exhibited a large electroactive surface area with a specific activity of 21.74 mA cm −2 and a If /Ir of 1.23, which were higher than those of traditional ethanol electrocatalysts. The catalyst also presented better catalytic performance for ethanol oxidation, excellent stability and anti‐poisoning ability. Abstract : Using NiFe‐LDH with a "card house" as the carrier and supported with Pt3 Sn nano‐alloy particle catalyst, the dispersion of Pt3 Sn NPs was effectively enhanced. The effective synergistic effect between LDH carrier and Pt3 Sn NPs significantly enhanced the catalytic activity of the catalyst for ethanol.